Low Salicylic Acid Level Improves Pollen Development Under Long-Term Mild Heat Conditions in Tomato - Jansma, Stuart Y.; Sergeeva, Lidiya I.; Tikunov, Yury M.; Kohlen, Wouter; Ligterink, Wilco; Rieu, Ivo (Frontiers in Plant Science, 2022)
Exposure to high temperatures leads to failure in pollen development, which may have significant implications for food security with ongoing climate change. We hypothesized that the stress-response-associated hormone salicylic acid (SA) affects pollen tolerance to long-term mild heat (LTMH: ≥14 days exposure to day-/nighttime temperature of 30-34/24-28°C, depending on the genotype), either positively, by inducing acclimation, or negatively, by reducing investment in reproductive development. Here, we investigated these hypotheses assessing the pollen thermotolerance of a 35S::nahG tomato line, which has low SA levels. We found that reducing the SA level resulted in increased pollen viability of plant grown in LTMH and further characterized this line by transcriptome, carbohydrate and hormone analyses. Low expression of JAZ genes in 35S::nahG and LTMH hypersensitivity of low-jasmonic acid (JA) genotypes together suggest that the increased pollen thermotolerance in the low-SA line involves enhanced JA signal in developing anthers in LTMH. These findings have potential application in the development of more thermotolerant crops.